Peak Abundance of Fatty Acids From Intertidal Biofilm in Relation to the Breeding Migration of Shorebirds - Schnurr, Peter J.; Drever, Mark C.; Elner, Robert W.; Harper, John; Arts, Michael T. (Frontiers in Marine Science, 2020)
Intertidal biofilm is a thin layer of microbes and meiofauna enmeshed in an extracellular polymeric matrix within and on top of mudflat sediment. This medium provides a dynamic resource for a variety of consumers in estuarine habitats, and is rich in essential fatty acids that birds require for long-distance migration. We measured seasonal changes in biofilm fatty acid content from spring to summer on the Fraser River Estuary, one of the richest and most important ecosystems for migrant and wintering waterbirds in Canada. Fatty acid content in biofilm showed a strong seasonal pattern with a peak in the spring that is associated with the northward migration of Western Sandpipers (Calidris mauri) to their breeding grounds. This peak is linked to the abundance and physiological state, and hence nutritional condition of epipelic diatoms, which, in turn, depend on a combination of mudflat topography, salinity, temperature, and nutrients that can fluctuate widely with the freshwater inputs from the Fraser River. Specifically, areas with higher elevation (i.e. 1 m) had longer periods of exposure to ambient conditions (i.e. light, warm temperatures, gas exchange into/out of biofilms) that facilitated more biofilm growth and higher fatty acid content. Moreover, springtime changes in water chemistry (i.e. salinity/osmotic stresses and nutrients) and temperature facilitated the production of higher overall total lipid/fatty acid contents in the mudflat biofilms compared to summer. Effective conservation of migrating shorebirds depends on the protection of underlying processes at important stopover sites that promote biofilm communities to escalate their production of lipids including essential fatty acids during key times of the year.